2017
DOI: 10.1080/03719553.2017.1375767
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of factors influencing freeze lining behaviour

Abstract: Recent studies have indicated that the steady state thicknesses and interface temperatures of freeze linings can be influenced by factors other than the thermal parameters of the systems. To explore these possibilities further cold modelling of freeze linings was undertaken in the CaCl 2 -H 2 O system using an experimental apparatus that enabled the variation of both the bath temperature and the fluid flow rate. Through in situ experimental observations, it was shown that the phases formed, the deposit/liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…They found that the thickness of the freeze-lining, the interface temperature, and the phases which formed during solidification were sensitive to the parameters that determine the chemical driving force, but not very sensitive to the bulk fluid velocity. [23] In earlier work by Crivits et al they found that lower viscosity results in higher interface temperature at the freeze-lining. It was also confirmed further that the thinnest areas of the freeze-lining occur in the areas of high turbulence, as previously suggested by Fraser et al [24,25] In the present study, a numerical model was established to aid in the design of a slag transfer system which can form a complete freeze-lining.…”
Section: Introductionmentioning
confidence: 93%
“…They found that the thickness of the freeze-lining, the interface temperature, and the phases which formed during solidification were sensitive to the parameters that determine the chemical driving force, but not very sensitive to the bulk fluid velocity. [23] In earlier work by Crivits et al they found that lower viscosity results in higher interface temperature at the freeze-lining. It was also confirmed further that the thinnest areas of the freeze-lining occur in the areas of high turbulence, as previously suggested by Fraser et al [24,25] In the present study, a numerical model was established to aid in the design of a slag transfer system which can form a complete freeze-lining.…”
Section: Introductionmentioning
confidence: 93%
“…The timing and thickness of the ice bath can also impact hydrologic responses in Arctic lakes, which may have implications for ice bath application as a recovery strategy (Arp, 2015) (18). Finally, chemical parameters can influence freeze lining behavior, which suggests a potential avenue for further exploration in the context of ice bath interventions (Crivits, 2018) (19). Collectively, these findings emphasize the complexity of factors that contribute to the conflicting outcomes in this area.…”
Section: Controversies and Variability In Responses: The Need For Pre...mentioning
confidence: 98%
“…The melting phase diagram for the different salt hydrate‐water system (Ba(OH) 2 ‐H 2 O, CaCl 2 ‐H 2 O, Ca(NO 3 ) 2 ‐H 2 O, Cd(NO 3 ) 2 ‐H 2 O, CH 3 COONa‐H 2 O, KF‐H 2 O, LiClO 3 ‐H 2 O, LiNO 3 ‐H 2 O, MgCl 2 ‐H 2 O, Mg(NO 3 ) 2 ‐H 2 O, Mn(NO 3 ) 2 ‐H 2 O, Na 2 CO 3 ‐H 2 O, Na 2 HPO 4 ‐H 2 O, NaOH‐H 2 O, Na 2 SO 4 ‐H 2 O, Na 2 S 2 O 3 ‐H 2 O, NH 4 Al(SO 4 ) 2 ‐H 2 O, and Zn(NO 3 ) 2 ‐H 2 O) along with their thermophysical properties (melting temperature, specific heat, thermal conductivity, density, the heat of fusion, and viscosity) in both phases were reported 32 . Region for all possible formation of hydrates of CaCl 2 and Zn(NO 3 ) 2 from its salt solution was reported from its melting phase diagram of CaCl 2 ‐H 2 O 32,33 and Zn(NO 3 ) 2 ‐H 2 O, 13,32 respectively. Different concentrations of saturated aqueous salt solutions can be used as PCM to get a wide phase change temperature range.…”
Section: Mechanism Of Heat Transition In Salt Hydrates During the Phamentioning
confidence: 99%